2016
DOI: 10.1155/2016/6796270
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal Stimulus Intensity as a Diagnostic Tool in Chronic Demyelinating Neuropathy

Abstract: Objective. The ability to correctly identify chronic demyelinating neuropathy can have important therapeutic and prognostic significance. The stimulus intensity value required to obtain a supramaximal compound muscle action potential amplitude is a commonly acquired data point that has not been formally assessed as a diagnostic tool in routine nerve conduction studies to identify chronic neuropathies. We postulated that this value was significantly elevated in chronic demyelinating neuropathy. Methods. We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Likewise, the required stimulus to reach supramaximal stimulus in these cases was similar for fore- and hindlimbs and varied between 5-12 mA. In CMT, the requirement for increased stimulus intensities has been recognized 17 and the same phenotype was seen in C61-PMP22 mice ( Figure 4C ). The phenomenon has been explained by increased electrical impedance from hypertrophic endoneurial changes 17 .…”
Section: Representative Resultsmentioning
confidence: 80%
“…Likewise, the required stimulus to reach supramaximal stimulus in these cases was similar for fore- and hindlimbs and varied between 5-12 mA. In CMT, the requirement for increased stimulus intensities has been recognized 17 and the same phenotype was seen in C61-PMP22 mice ( Figure 4C ). The phenomenon has been explained by increased electrical impedance from hypertrophic endoneurial changes 17 .…”
Section: Representative Resultsmentioning
confidence: 80%
“…In CMT1a patients, motor axon hypoexcitability was particularly pronounced and systematically concerned the three studied parameters (minimal threshold, iUP, iMAX) at the three stimulation sites which was not the case for CIDP patients (Table 7). In a very similar approach (stimulus intensity value required to obtain a supramaximal CMAP), although retrospective, Parker et al (2016) observed in median and ulnar studies that mean supramaximal intensities were significantly higher in patients with CMT and CIDP than normal controls. Many studies have also been conducted using Qtrac software (threshold tracking techniques) to study motor nerve excitability in demyelinating neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the required stimulus to reach supramaximal stimulus in these cases was similar for fore-and hindlimbs and varied between 5-12 mA. In CMT, the requirement for increased stimulus intensities has been recognized 17 and the same phenotype was seen in C61-PMP22 mice (Figure 4C). The phenomenon has been explained by increased electrical impedance from hypertrophic endoneurial changes 17 .…”
mentioning
confidence: 80%